A Simple PCR–RFLP Method for Genetic Phase Determination in Compound Heterozygotes - Perry, Rodney T.; Dwivedi, Harsh; Aissani, Brahim (Frontiers in Genetics, 2012)
When susceptibility to diseases is caused by cis-effects of multiple alleles at adjacent polymorphic sites, it may be difficult to assess with confidence the genetic phase and identify individuals carrying the risk haplotype. Experimental assessment of genetic phase is still challenging and most population studies use statistical approaches to infer haplotypes given the observed genotypes. While these statistical approaches are powerful and have been proven very useful in large scale genetic population studies, they may be prone to errors in studies with small sample size, especially in the presence of compound heterozygotes. Here, we describe a simple and novel approach using the popular PCR-RFLP based strategy to assess the genetic phase in compound heterozygotes. We apply this method to two extensively studied SNPs in two clustered immune-related genes: The -308 (G>A) and the + 252 (A>G) SNPs of the tumor necrosis factor alpha (TNF) and the lymphotoxin alpha (LTA) genes, respectively. Using this method, we successfully determined the genetic phase of these two SNPs in known compound heterozygous individuals and in every sample tested. We show that the A allele of TNF -308 is carried on the same chromosome as the LTA +252(G) allele.